2004
DOI: 10.1074/jbc.m403145200
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Induction of Insig-1 in White Adipose Tissue Reveals a Novel Interplay of Peroxisome Proliferator-activated Receptor γ and Sterol Regulatory Element-binding Protein in the Regulation of Adipogenesis

Abstract: Insulin-induced gene 1 (INSIG-1) is a key regulator in the processing of the sterol regulatory element-binding proteins (SREBPs). We demonstrated that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
78
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 31 publications
6
78
0
Order By: Relevance
“…In the nucleus, the mature form of SREBP-1c is able to bind to specific sequences (sterol-regulatory elements SRE and E-boxes) located in the promoter gene of SREBP target genes (Figure 1.1). (Fig.1) (6). Considering that INSIG-1 appears to inhibit lipo-and adipogenesis, it is hard to reconcile this observation with the pro-adipogenic role of PPAR (9).…”
Section: Transcriptional Regulation Of Lipogenesis In Adipose Tissuementioning
confidence: 99%
“…In the nucleus, the mature form of SREBP-1c is able to bind to specific sequences (sterol-regulatory elements SRE and E-boxes) located in the promoter gene of SREBP target genes (Figure 1.1). (Fig.1) (6). Considering that INSIG-1 appears to inhibit lipo-and adipogenesis, it is hard to reconcile this observation with the pro-adipogenic role of PPAR (9).…”
Section: Transcriptional Regulation Of Lipogenesis In Adipose Tissuementioning
confidence: 99%
“…INSIG-1 is a central regulator in the processing of sterol regulatory element binding proteins. Two animal studies demonstrated an antilipogenic effect of INSIG-1 in vitro and in vivo (23) and identified INSIG-1 as a peroxisome proliferator-activated receptor ␥ target gene, providing a link between insulin sensitization and glucose homeostasis as well as lipid homeostasis (24).…”
mentioning
confidence: 99%
“…However, the proposed USF binding site is not highly homologous to established SREs or E-boxes. Moreover, an SRE was recently described [34] in the human INSIG1 promoter (located between −545 and −536, see Fig. 2a), but an equivalent SRE sequence does not seem to be conserved in the mouse Insig1 promoter.…”
Section: Discussionmentioning
confidence: 95%